Nongraded versus Graded Elementary Schools: An Analysis of Achievement and Social Skills (Alberta Journal of Educational Research, 2000)
In the last decade nongraded schools have regained popularity. Researchers and practitioners question the impact of the present applications of the nongraded structure on students. Two separate studies were conducted that compared the effects of nongraded and graded school grouping structures. The first study analyzed academic outcomes in reading, math, written language, and spelling. The second study evaluated the relationship between school type and social skills. Results indicated that students in the primary level (grades 1, 2, and 3) who attended the nongraded school performed better than their counterparts in the graded school on the reading and math assessment, but there were no differences in written language or spelling. At the intermediate level (grades 4, 5, and 6), students at the nongraded school performed better in written language and spelling, but the scores did not differ in reading or math. Students in the nongraded schools reported a higher level of social skills than students at the graded schools. The results and implications for school practice are discussed.